2013
DOI: 10.1038/ncomms2378
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and robust induction of nephrogenic intermediate mesoderm from human pluripotent stem cells

Abstract: A method for stimulating the differentiation of human pluripotent stem cells (hPSCs) into kidney lineages remains to be developed. Most cells in kidney are derived from an embryonic germ layer known as intermediate mesoderm (IM). Here we show the establishment of an efficient system of homologous recombination in hPSCs by means of bacterial artificial chromosome (BAC)-based vectors and single nucleotide polymorphism (SNP) array-based detection. This system allowed us to generate human induced pluripotent stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
247
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(256 citation statements)
references
References 36 publications
6
247
2
1
Order By: Relevance
“…ME differentiation. ME differentiation was performed as described previously, with slight modification 37 . The single-cell suspensions of human pluripotent stem cells were plated onto Collagen I-coated plates (BD biosciences) in DMEM/F12 containing 2% B27, 100 ng ml À 1 Activin A, 3 mM CHIR99021 and 0.5% Pen/Strep.…”
Section: Methodsmentioning
confidence: 99%
“…ME differentiation. ME differentiation was performed as described previously, with slight modification 37 . The single-cell suspensions of human pluripotent stem cells were plated onto Collagen I-coated plates (BD biosciences) in DMEM/F12 containing 2% B27, 100 ng ml À 1 Activin A, 3 mM CHIR99021 and 0.5% Pen/Strep.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of the duration of CHIR pretreatment, the proportion of cells expressing PAX2 significantly decreased after day 4 of differentiation, with ,10% of cells at day 7 retaining PAX2 expression. Because previous studies have identified a role for BMP7 in inducing IM cells, 5,14,16,17 we next determined whether the addition of BMP7 to FGF2 and RA could enhance IM cell differentiation. In contrast to these other reports, we found that the addition of BMP7 significantly To determine the reproducibility of our protocol in different hPSC lines, we tested the combination of CHIR induction for 36 hours followed by the addition of FGF2 and RA in three hESC lines and two hiPSC lines.…”
Section: Fgf2 Induces Pax2 Expression In Chir-induced Cellsmentioning
confidence: 99%
“…[16][17][18][19] These previous reports have produced cells that share characteristics expected of human kidney progenitor or epithelial cells, although the identities of these differentiated cells have yet to be conclusively verified. In addition, the efficiencies of these protocols for generating cells of the renal lineage are low, necessitating the use of cell sorting to enrich populations of cells using markers that are not entirely specific to the kidney.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The induced nephron progenitor aggregates readily formed three-dimensional primordial glomeruli and renal tubules on Wnt stimulation in vitro, similar to those spontaneously observed in teratomas. 2 Importantly, like other recent in vitro renal differentiation protocols, 6 Nishinakamura and colleagues 3 use iPSCs generated according to the Yamanaka method as the starting material, potentially affording patient-derived autologous cells rather than allogeneic cells for transplant and the possibility of personalized renal medicine.…”
mentioning
confidence: 99%